Roquefornine A, a sesterterpenoid with a 5/6/5/5/6-fused ring system from the fungus Penicillium roqueforti YJ-14. Issue 12 (12th May 2020) - Wang, Jia-Peng; Shu, Yan; Hu, Jun-Tao; Liu, Rui; Cai, Xue-Yun; Sun, Cheng-Tong; Gan, Dong; Zhou, Di-Jiao; Mei, Rui-Feng; Ding, Hao; Zhang, Xiao-Ran; Cai, Le; et al.
Abstract : Roquefornine A, a sesterterpenoid with an unprecedented 5/6/5/5/6-membered pentacyclic system, was characterized from Penicillium roqueforti YJ-14. Abstract : Roquefornine A, a sesterterpenoid with an unprecedented 5/6/5/5/6-membered pentacyclic system, was characterized from Penicillium roqueforti YJ-14. Its structure was determined by extensive spectroscopic analyses, [Rh2 (OCOCF3 )4 ]-induced CD data, and DP4+ calculations. A biosynthetic pathway, cytotoxicity, and anti-inflammatory activity were also discussed.